Revitalizing mathematics education preparation in Nigeria for national development: an innovative view (2018)
Mathematics education currently is not in a good phase as regard its product in term of marketability, teachers’ quality, subject mastery, professional competent, pedagogical acumen among others. National development in the context of teacher preparation and other so called in Nigeria should be seen within perspective of overall progress because national development embodies the overall gross progress people achieve within the context of its economic, political and socio–cultural potential. It has since become an undisputable fact that education is one of the potent tool for social transformation for national development anywhere in the world and in all sphere of political system. It is therefore imperative to look critically at different ways to revitalize Mathematics education preparation in Nigeria with reference to national development and putting up various innovations and think–thank syndrome into pre-service teacher preparation.